Kemenag dan Sengketa Masjid di Kota Kediri - Atira, Siti Mashita (Journal of Islamic and Social Studies, 2023)
Land disputes are a classic issue and are always everywhere on the face of the earth. Therefore, land-related disputes are constantly going on because every human being has an interest related to land. Of the many waqf land disputes that have occurred, there is a special waqf land dispute that occurs in manisrenggo kediri city, where there has been a struggle for waqf land. Therefore, researchers are interested in studying how the Strategy of the Kediri City Ministry of Religion in Justice Sengeketa Masjid Al-Muttaqun in Manisrenggo District, Kediri City. The research aims to explore the role of the strategy of the Ministry of Religion of the Republic of Indonesia, Kediri City in Justice Sengeketa Masjid Al-Muttaqun in Manisrenggo District, Kediri City. In analyzing these problems, researchers use quality research methods with a descriptive approach. Of course, the results of the research were obtained, namely the strategy that had been carried out by the Ministry of Religion of the Republic of Indonesia, Kediri City, mainly and various parties were unsuccessful in the mediation process from both parties to the dispute over the waqf land. But the matter has reached the courts which are still ongoing.